Mandatory Sentencing Guidelines: The Case Of Macedonia - Gordana Lazetic Buzarovska; Nikola Tupanceski; Elena Mujoska (European Scientific Journal, ESJ, 2016)
This study expresses the criticism of recently enacted Law in determining the type and in measuring the severity of sentence. There is flagrant restriction of the free judicial belief due to the necessity in overcoming identified inconsistency in sentencing policy. The judicial system is not resistant to both internal and external pressures and influences. However, those problems cannot be overcome by massive fragmentation of the Criminal Code of the Republic of Macedonia, wide ranges of the sanctions, and by administrative proceedings in the determination of the sanction. New Macedonian law has created mandatory guidelines for every criminal offence by emphasizing previous conviction as the most important circumstances. This is contrary to several Council of Europe recommendations. The authors emphasize that the binding character of the sentencing guidelines should be avoided. According to them, only free judicial belief within the statutory penal framework can ensure the rule of the law and equity.